Adjudicating the logistics of COVID-19 vaccine boosters from a global perspective. Issue 1 (31st January 2022) - Priyanka,; Choudhary, Om Prakash; Singh, Indraj
ABSTRACT: The emergence of the novel SARS-CoV-2 variants has led to the advocation of COVID-19 vaccine boosters by many countries. The reasons cited for the booster vaccination, such as waning immunity, immune escape due to viral evolution and suboptimal responses in immunocompromised individuals, need to be cautiously weighed against possible risks, including immune-mediated side effects, vaccine hesitancy, global vaccine inequity, and emergence of new variants in the naive population. The scientific, ethical, and economic adjudication indicates that the primary vaccination of unvaccinated masses should be prioritized over the premature booster implementation. Although, in the future, when the global vaccine shortage has been subdued or if the protective immunity afforded by the current COVID-19 vaccination protocols wanes substantially, the booster vaccinations may be implemented.